The rheological and microstructural properties of pea, milk, mixed pea/milk gels and gelled emulsions designed by thermal, acid, and enzyme treatments. (April 2018) - Ben-Harb, S.; Panouillé, M.; Huc-Mathis, D.; Moulin, G.; Saint-Eve, A.; Irlinger, F.; Bonnarme, P.; Michon, C.; Souchon, I.
Abstract: The rheological and microstructural properties of pure pea, pure milk, and mixed pea/milk gels were investigated and compared. Three gelation techniques were used: a thermal treatment, an acid treatment employing glucono delta-lactone, and an enzyme treatment employing chymosin and transglutaminase. Considerable differences in the gels' rheological and microstructural properties were observed. The thermally induced pure pea and mixed gels had comparable rheological and microstructural properties, suggesting the existence of interactions between pea and whey proteins. The enzyme-induced gels had a higher strain at rupture, a property that was associated with the presence of coarse aggregates. Within this gel type, mixed gels displayed a lower storage modulus than did pure pea or pure milk gels. Among acid-induced gels, pure pea gels were much stiffer than pure milk or mixed gels, probably because their final pH was lower. The addition of fat strengthens the mechanical properties of all pea gels studied, in particular in the mixed gels obtained by acid and enzyme gelation. The microstructural differences were consistent with the rheological differences. These results provide insight into the formation of gels via these gelation techniques and could inform the formulation of new food products that are enriched in plant protein. Graphical abstract: Image 1 Highlights: Gels were obtained from pea and milk proteins using thermal, acid, and enzyme treatments. The rheological and microstructural properties of gels were treatment dependent. Interactions occurred between pea and whey proteins during the thermal treatment. Enzyme-induced gels had a higher strain at rupture. The acid-induced pure pea gel was the stiffest.